(untitled) (Journal of Hama University, 2020)
This study aimed to identify the role of underwriting, liquidity and capital risk management in improving the financial performance of private insurance companies listed on the Damascus Stock Exchange. To achieve this purpose, the annual data have collected from five private commercial insurance companies listed on the Damascus Stock Exchange during the period between 2008 and 2018. The data were collected from the financial statements of the insurance companies. Improving financial performance represented dependent variable and measured using the rate of return on assets, rate of return on equity, and the percentage of leverage. While the independent variables represented by underwriting risk, liquidity risk and capital risk were measured using the following ratios (net written premiums to shareholders’ equity, liabilities to liquid assets, available capital to required capital) respectively. To achieve the purpose of the study, one of the Panel Data models, this is the Random Effects Model, used to test the relationship between the independent variables and the dependent variable. Data analyzed based on E-Views 10 statistical program. Results of the study showed a positive significant correlation between liquidity risk management and improving financial performance when it measured by the percentage of financial leverage, the study also showed an negative correlation significant between capital risk management and improving financial performance when it measured by the rate of financial leverage, while the study resulted that, There is no significant relationship between managing underwriting risks and improving the financial performance of the companies studied.